SINTESIS DAN KARAKTERISASI KARBON AKTIF DARI PREKURSOR BATUBARA - Septiana, Atut Reni; Teluma, Yosef Christian Riki; Rifani, Agus (Universitas Mataram, 2022)
In this work, coal derived activated carbon has been synthesized successfully. The activated carbon was prepared by soaking coal powder in KOH solution and continued by activation at varied temperature, i.e. 400, 500, and 600ËšC. The performance of the activated carbon was examined by X-Ray Diffraction (XRD), Fourier Transform Infrared spectroscopy (FTIR), moisture content, and iodine adsorption. The XRD data analysis results indicated the amorphous structure of carbon and revealed the more amorphous carbon as the higher of the activation temperature. The characterization using FTIR exhibited the presence of functional groups such as hydroxyl, carboxylic acid, ketone, amino, and so on. The lowest moisture content was achieved by activated carbon which was activated at 400ËšC, namely 3.77%, while the moisture content for activation temperature at 500 and 600ËšC were 5.3 and 7.74 % respectively. Moreover, the adsorption of iodine increased by the increase of the activation temperature due to high pore surfaces of the activated carbon